2020
DOI: 10.1093/tas/txaa057
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sow lactation feed intake on the growth and suckling behavior of low and average birthweight pigs to 10 weeks of age

Abstract: Improved genetics in commercial pig production have resulted in larger litter sizes. However this has increased the prevalence of compromised pigs exhibiting inferior birthweights, weaning weights, and lifetime performance. This study aimed to determine the effects of increased sow lactation feed intake on growth of low and average birthweight piglets until 10 wk of age. Low (Low BW; <1 kg) and average (Av BW; 1.3–1.7 kg) birthweight animals were reared in uniformly weighted litters comprising 14 piglet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
1
16
2
1
Order By: Relevance
“…Growth performance during the suckling period is typically influenced by factors from sows (birth weight, milk yield and milk composition) and form piglets (milk intake) (White et al, 1984;Hawe et al, 2020;Hojgaard et al, 2020). However, our results showed that average birth weight was not different all year round.…”
Section: Seasonal Effect On Piglet Performancecontrasting
confidence: 69%
“…Growth performance during the suckling period is typically influenced by factors from sows (birth weight, milk yield and milk composition) and form piglets (milk intake) (White et al, 1984;Hawe et al, 2020;Hojgaard et al, 2020). However, our results showed that average birth weight was not different all year round.…”
Section: Seasonal Effect On Piglet Performancecontrasting
confidence: 69%
“…Furthermore, improved sow lactation nutrition can significantly reduce pre weaning mortality of low birth weight animals. This, in turn, will greatly increase the number of animals weaned, improving output and profitability at farm level [21]. Therefore, by weighing all litters at 21 days of age, sows' milk can be monitored.…”
Section: Resultsmentioning
confidence: 99%
“…Eissen et al [ 28 ] showed that litter weight gain increased as feed intake of the sows increased. Moreover, Hawe et al [ 29 ] estimated the effect of increasing sow feed intake on piglet growth and showed that better sow feeding during lactation can increase milk yields and piglet weaning weights. In our analyses using the IC algorithm, we observed a non-directed edge between dLFI and dLWG, which disappeared when HPD 95% were used instead of HPD intervals with smaller levels of probability content.…”
Section: Discussionmentioning
confidence: 99%